"Where my pocket can afford is where I will take my child". The influence of structural factors on the health-seeking behaviour of the population in Gorama Mende and Wandor chiefdoms, Kenema district, Sierra Leone - Doris Burtscher; Anna Christina Maukner; Margerita Piatti; Jesse Verschuere; Tamba Magnus Aruna; Olga Em; Gbane Mahama; Annick Antierens (Elsevier, 2022)
In Sierra Leone, maternal and under-five mortality rates are among the highest in the world. In 2010, the government adopted the Free Healthcare Initiative (FHCI) providing free healthcare for children aged under-five and pregnant and lactating women. However, the FHCI is seriously impeded by the limited availability of health staff, gaps in medication supply, and weak management. In this paper, we present experiences of the Gorama Mende and Wandor (GMW) chiefdom residents in Kenema district, Sierra Leone and how they navigate available options to seek care. We argue that the health-seeking behaviour (HSB) of the population is influenced by interrelated structural and social factors. This qualitative research was conducted in rural GMW chiefdoms in February 2020, using in-depth individual, paired, and group interviews. Contrary to the assumption that traditional healers influence HSB, data suggest that structural factors like proximity, affordability, previous experience, and reception at the health facility were the main determinants. Healthcare providers felt that people went to a traditional healer first; however, the population emphasised that their first choice was always the peripheral health unit (PHU) provided there were no barriers. These barriers include, living in hard-to-reach areas, transportation, unexpected payment for services, and fear of the health staff. The study reveals the complex reality people face in terms of access to healthcare and multiple factors that influence HSB. One community member noted that if people could not afford a PHU, they would turn to alternative forms of healthcare - 'Where my pocket can afford is where I will take my child'.